2018
DOI: 10.1017/s0305000918000120
|View full text |Cite
|
Sign up to set email alerts
|

Look before you speak: children's integration of visual information into informative referring expressions

Abstract: Children's ability to refer is underpinned by their developing cognitive skills. Using a production task (n=57), we examined pre-articulatory visual fixations to contrast objects (e.g. to a large apple when the target was a small one) to investigate how visual scanning drives informativeness across development. Eye movements reveal that although four-year-olds fixate contrast objects to a similar extent as seven-year-olds and adults, this does not result in explicit referential informativeness. Instead, four-y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…It also comports with the observation that children are more likely to be adequately informative in studies where the listener is an actual person with “real” informational needs (whether a confederate of the experimenter's—Bahtiyar & Küntay, ; Grigoroglou & Papafragou, ; Nadig & Sedivy, ; Nilsen & Graham, ; or a naïve participant—Köymen et al, ; O'Neill, ; Perner & Leekam, ) as opposed to an imaginary addressee or no specific addressee at all (e.g., Davies & Katsos, ; Girbau, ; cf. Davies & Kreysa, ; Rabagliati & Robertson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also comports with the observation that children are more likely to be adequately informative in studies where the listener is an actual person with “real” informational needs (whether a confederate of the experimenter's—Bahtiyar & Küntay, ; Grigoroglou & Papafragou, ; Nadig & Sedivy, ; Nilsen & Graham, ; or a naïve participant—Köymen et al, ; O'Neill, ; Perner & Leekam, ) as opposed to an imaginary addressee or no specific addressee at all (e.g., Davies & Katsos, ; Girbau, ; cf. Davies & Kreysa, ; Rabagliati & Robertson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several different explanations for children's underinformative production have been proposed. One possibility is that children omit information needed by addressees because, unlike adults, they fail to direct their attention to critical scene components that should find their way into grammatical encoding (for discussion on the relation between scene apprehension and linguistic production in children, see Bunger et al, ; Davies & Kreysa, ; Deutsch & Pechmann, ; Pechmann, ; Whitehurst, ; Whitehurst & Sonnenschein, ). Despite the plausibility of this explanation, recent eye‐tracking studies with children have shown that eye‐gaze patterns do not always predict which scene component will be mentioned in production (e.g., Bunger et al, ; Davies & Kreysa, ; cf.…”
Section: Introductionmentioning
confidence: 99%
“…We further manipulated the complexity of displays in two ways: we either included the symmetrical competitor, creating more complex displays, or excluded it, creating less complex displays (for a similar approach using a contrast manipulation, see Davies & Kreysa, 2017, 2018; Sedivy, Tanenhaus, Chambers, & Carlson, 1999). We therefore decreased display complexity when a symmetrical competitor was absent due to its high degree of visual similarity to the left/right target picture.…”
Section: Visual World Production Eye-tracking Paradigmmentioning
confidence: 99%
“…The lack of contrastive usage may also limit the extent to which children scan the visual environment, again because the CDS they hear does not cue comparison. Indirectly, this may account for young children's habitual use of under-informative referring expressions in production (Davies & Katsos, 2010;Davies & Kreysa, 2018;Matthews, Butcher, Lieven, & Tomasello, 2012;Matthews, Lieven, & Tomasello, 2007).…”
Section: Discussionmentioning
confidence: 99%